Adaptive Interpolated PI Gain Scheduling for Voltage Regulator in Solar Charge Controller Applications - Samman, Faizal Arya; Hamka, Dea Fatriziah; Diatmika, Made Dharma Budy; Sahali, Ida Rachmaniah (E3S web of conferences, 2018)
Buck-boost converter is one of the dc-dc convert0.er that can both increase and decrease the value of output voltage. Due to its wide output range, this converter is very appropriate for using in solar-based electric generation systems. To control the stable expected output voltage, this converter is usually integrated with feedback control. One of the old and widely used control techniques is PID control. However, conventional PID controls still have deficiencies, because the parameters of PID parameters are static so that for wide ranges of input or load will provide different transient responses. This paper will present a new PI control with an adaptive interpolated PI gain scheduling technique. The proposed control algorithm has been embedded and implemented in real microcontroller hardware and its performance has been tested under load change conditions, and the input voltage changes within the range of 8-22 V. Testing results show that PI control with gain scheduling technique produces better transient response compared to the traditional fixed PI controller. The time domain transient response measurements, under load changes within the range of 20-1000 Ohm, present that the proposed control algorithm give settling time value below 1.0 second, rise-time below 0.436 second, maximum overshoot below 0.5%, and the steady-state error below 0.3 V.